Effectiveness of clobazam as add-on therapy in children with refractory focal epilepsy Eficácia do clobazam como terapia adjuvante em crianças com epilepsia focal refratária - Mariana Ribeiro Marcondes da Silveira; Maria Augusta Montenegro; Renata Cristina Franzon; Carlos A.M. Guerreiro; Marilisa M. Guerreiro (Arquivos de Neuro-Psiquiatria)
The objective of this study was to evaluate the safety and efficacy of clobazam in children with refractory focal epilepsy. We investigated 100 consecutive patients concerning etiology of epilepsy, previously used antiepileptic drugs, seizure frequency and adverse events. Clobazam was introduced as add-on therapy in patients with previous failure of at least two monotherapies. Mean age was eight years-old and 39 patients were girls. Clobazam mean dosage was 23.6 mg/day. Mean use of clobazam was 18.6 months. Twenty-two patients had adverse events. Twenty-six patients became seizure-free, 11 had an improvement of >75% and in 58 there was no modification in seizure frequency. Five patients had an increase in seizure frequency. Clobazam efficacy lasted for more than one year in 42% of the seizure-free patients. Clobazam seems to be safe and effective in the treatment of focal epilepsy in childhood and should be considered in patients with refractory seizures. O objetivo deste estudo foi avaliar a segurança e eficácia do clobazam em crianças com epilepsia focal refratária. Nós investigamos 100 pacientes consecutivos em relação à etiologia da epilepsia, uso prévio de drogas anti-epilépticas, freqüência de crises e eventos adversos. Clobazam foi introduzido como terapia adjuvante em pacientes que não responderam a pelo menos duas monoterapias. A idade média foi 8 anos e 39 pacientes eram do sexo feminino. A dose média de clobazam foi 23,6 mg/dia. O uso médio de clobazam foi por 18,6 meses. Vinte e dois pacientes tiveram eventos adversos. Vinte e seis pacientes tornaram-se livres de crises, 11 tiveram melhora > 75% e em 58 não houve modificação na freqüência de crises. Cinco pacientes tiveram aumento na freqüência de crises. A eficácia do clobazam permaneceu por mais de um ano em 42% dos pacientes sem crises. Clobazam parece ser seguro e eficaz no tratamento de epilepsia focal na infância e deve ser considerado em pacientes com crises refratárias.